Managerial marketing and behavioral marketing: when myths about marketing management and consumer behavior lead to a misconception of the discipline - Manfred Bruhn; Andrea Gröppel-Klein; Manfred Kirchgeorg (Journal of Business Economics, 2023)
Marketing has become accepted and proven in science and practice over the past decades. Many principles of marketing have become self-evident, but have led to gross generalizations and simplified thought patterns. This article examines myths and metaphors in marketing. A distinction is made between myths of managerial marketing and of behavioral marketing. In both sub-disciplines, we are often dealing with complex and invisible phenomena that occur in a variety of contexts. Attempts to explain these phenomena are therefore particularly prone to the emergence of myths or misconceptions. From a managerial perspective, topics such as the philosophy and leadership role of marketing, the generation of innovation success, the development of strategic competitive advantages, and brand management are reflected. Since the change from a sellers' market to a buyers' market, consumer behavior research and marketing have been closely intertwined. Therefore, findings from consumer behavior research form a central basis for successful decisions in marketing management. Based on this background, the second part of the article focuses on myths of consumer behavior research, here~addressing unconscious phenomena in consumer behavior,~mainly the discussion~of subliminal priming (and its impact on manipulation)~and unconscious perception~as well as of unconscious motives, and approaches to implicite~attitude measurement. Finally, implications are derived as to what extent the presented phenomena and the unveiling of myths have an impact on marketing management~and on consumer behavior research and what roles these disciplines~should take in the future. In the era of climate change and digital transformation, particular challenges are emerging. Thus, facts and not myths should determine the future path of the marketing discipline.
Keywords: M3; 650; Consumer behavior research; Attitudes; implicit and explicit; IAT; implicit~motives; Innovation; Priming; Purchase decisions; Brand management; Marketing management; Misconceptions; Myths; Priming effects; Subliminal manipulation; Psychology; Unconscious~behavior; Competitive advantage